Efficacy of Geo-Cellular Mat (GCM) to mitigate settlement via field performance - Tuan Ismail, Tuan Noor Hasanah; Wijeyesekera, Devapriya Chitral; Bakar, Ismail; Kasalan, As-Shar; Meng Siang, Alvin John Lim; Abdullah, Mohd Akmal (2021)
Road construction over soft yielding ground like peat soil presents a considerable technical challenge. Therefore, the soil needs to be stabilised to improve its geotechnical properties and to ensure the embankments constructed on it are stable and strong without risking excessive settlement and bearing failure. Recently, more attention has been given to lightweight fill materials as an alternative technology for road construction over soft ground. Hence, the development and use of innovative green technology products to meet the current pressing geo-environmental challenges are critically examined in this study. The main purpose of this paper is to evaluate the settlement behaviour of geo-cellular mat (GCM) block and compared the response from conventional natural fill material (sand fill). This is followed by the conceptual development of a GCM block by recycling plastic. GCM is lighter, stronger, and stiffer, which has a density of 125 ± 10 kg/m3, compressive strength in the range of 2.8 to 4.5 MPa, and stiffness in the range of 100 to 150 MPa were measured via axial compression test. A series of field test was conducted to simulate a particular cross-section of road embankment with a uniform static load for nearly a year to verify the effectiveness of GCM. The settlement plate gauges were used to determine the total ground movement beneath the fill loading at the interface between fill materials and subgrade surface. The findings of this study successfully prove the efficacy of the GCM block to diminish settlements over peat ground, compared with sand fill. The results show that the maximum absolute settlement and differential settlement were reduced by 35% and 70%, respectively with the application of GCM technology.